Defend our men in blue - Abd Razak, Dzulkifli (2006)
WHEN constable Mahadir Tawile, 24, was shot dead on Sept 18 as a result of a "friendly fire" during a police operation against a notorious robbery gang in Mentakab, Pahang, it did not hit the front pages of most newspapers. Yet, it is very fresh in one’s mind how just about any story about police is front page news not only by most newspapers but also hogs the headlines for weeks on end. Recall the classical nudesquat or the bald heads controversies. How about some alleged brutality, corruption, or that petty crimes are on the rise.